Biochemical insight into physiological effects of H 2S: Reaction with peroxynitrite and formation of a new nitric oxide donor, sulfinyl nitrite - Filipovic, Milos; Miljkovic, Jan; Allgäuer, Andrea; Chaurio Gonzalez, Ricardo Alfredo; Shubina, Tatyana; Herrmann, Martin; Ivanovic-Burmazovic, Ivana (Biochemical Journal, 2012)
The reaction of hydrogen sulfide (H S) with peroxynitrite (a key mediator in numerous pathological states) was studied in vitro and in different cellularmodels. The results show that H S can scavenge peroxynitrite with a corresponding second order rate constant of 3.3±0.4×10 M · s at 23°C (8± 2×10 M · s at 37°C). Activation parameters for the reaction (ΔH‡, ΔS‡ and ΔV‡) revealed that the mechanism is rather associative than multi-step free-radical as expected for other thiols. This is in agreement with a primary formation of a new reaction product characterized by spectral and computational studies as HSNO (thionitrate), predominantly present as sulfinyl nitrite, HS(O)NO. This is the first time a thionitrate has been shown to be generated under biologically relevant conditions. The potential of HS(O)NO to serve as a NO donor in a pH-dependent manner and its ability to release NO inside the cells has been demonstrated. Thus sulfide modulates the chemistry and biological effects of peroxynitrite by its scavenging and formation of a new chemical entity (HSNO ) with the potential to release NO, suppressing the pro-apoptotic, oxidative and nitrative properties of peroxynitrite. Physiological concentrations of H S abrogated peroxynitrite-induced cell damage as demonstrated by the: (i) inhibition of apoptosis and necrosis caused by peroxynitrite; (ii) prevention of protein nitration; and (iii) inhibition of PARP-1 [poly(ADP-ribose) polymerase 1] activation in cellular models, implying that a major part of the cytoprotective effects of hydrogen sulfide may be mediated by modulation of peroxynitrite chemistry, in particular under inflammatory conditions. © The Authors Journal compilation © 2012 Biochemical Society.